THE IMPORTANCE OF MOTIVATION IN LANGUAGE LEARNING (ESA FOR KEEPING MOTIVATION) - Sosiowati, I G. A. G (Lingual: Journal of Language and Culture, 2013)
Motivation, which is the drive to do something is considered to be very important in any learning, including language learning. It is the want of someone to do something. Someone with lack of motivation will never be successful in doing things. This idea leads to the situation that a language teacher should also be able to keep the studentsâ motivation high. It is the reSponsibility of the teachers to keep the motivation through their behavior towards the students, through their attitude while applying the methods of Engage, Study, Activate (ESA). It cannot be expected that all institutions all over the world are able to provide sophisticated teaching aid, however with good teachers who are capable of motivating students or keeping their already existing motivation high, successful learning can be achieved.